Widening Socioeconomic, Racial, and Geographic Disparities in HIV/AIDS Mortality in the United States, 1987–2011 - Singh, Gopal K. (Hindawi Publishing Corporation, 2013)
This study examined the extent to which socioeconomic and racial and geographic disparities in HIV/AIDS mortality in the United States changed between 1987 and 2011. Census-based deprivation indices were linked to county-level mortality data from 1987 to 2009. Log-linear, least-squares, and Poisson regression were used to model mortality trends and differentials. HIV/AIDS mortality rose between 1987 and 1995 and then declined markedly for all groups between 1996 and 2011. Despite the steep mortality decline, socioeconomic gradients and racial and geographic disparities in HIV/AIDS mortality increased substantially during the study period. Compared to whites, blacks had 3 times higher HIV/AIDS mortality in 1987 and 8 times higher mortality in 2011. In 1987, those in the most-deprived group had 1.9 times higher HIV/AIDS mortality than those in the most-affluent group; the corresponding relative risks increased to 2.9 in 1998 and 3.6 in 2009. Socioeconomic gradients existed across all race-sex groups, with mortality risk being 8–16 times higher among blacks than whites within each deprivation group. Dramatic reductions in HIV/AIDS mortality represent a major public health success. However, slower mortality declines among more deprived groups and blacks contributed to the widening gap. Mortality disparities reflect inequalities in incidence, access to antiretroviral therapy, and patient survival.